Livedo reticularis in type 2 lepra reaction: A rare presentation - Kikkeri Narayanasetty Naveen; Sharatchandra Bhimrao Athanikar; Spandana Prakash Hegde; Vidisha Sharatchandra Athanikar (Wolters Kluwer Medknow Publications, 2014)
Type 2 lepra reaction or erythema nodosum leprosum (ENL) is an immune complex syndrome that occurs mostly in lepromatous leprosy and sometimes in borderline lepromatous leprosy patients. We present an untreated case of lepromatous leprosy, who presented with type 2 lepra reaction and livedo reticularis. Livedo reticularis, though seen in lucio phenomenon, is not a part of type 2 lepra reaction. The case is being reported for its rarity.